Studi Meaning of Life Siswa SMP di Pondok Pesantren An-Nur II Al Murtadlo Bululawang Kabupaten Malang - Feny Andriyanti; Nur Hidayah; IM Hambali (Universitas Sebelas Maret, 2017)
Pondok pesantren is one of typical Indonesian Islamic educations, which have a philosophy as a way of life (meaning of life). The meaning of life will underlie the behavior of students in performing daily activities in order to achieve happiness. The aim of this research is to know the meaning of life achievement of the Junior High School students in pondok pesantren An-Nur II Al Murtadlo. This research used descriptive quantitative research design with survey method. The results of research showed that the Junior High School students in pondok pesantren An Nur II Al-Murtadlo have a high meaning of life with 63% percentage. However, there are three sources of value that have different achievement, the highest achievement is the values of experiential of love and religion, which is 37%, the values of attitudinal of striving, which is 34%, and the values of work creativity which is 29%. It can be interpreted that the experiential of love and religion values is the first contribution in the achievement of the meaning of life of the Junior High School students in pondok pesantren An-Nur II Al Murtadlo.